2008
DOI: 10.1007/s10803-007-0510-1
|View full text |Cite
|
Sign up to set email alerts
|

Language Assessment and Development in Toddlers with Autism Spectrum Disorders

Abstract: One of the primary diagnostic criteria for the diagnosis of autism spectrum disorders (ASD) is the presence of a language delay or impairment. Children with ASD are now being identified at significantly younger ages, and prior research has consistently found that early language skills in this population are heterogeneous and an important predictor for later outcome. The goal of this study was to systematically investigate language in toddlers with ASD and to identify early correlates of receptive and expressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
300
11
13

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(363 citation statements)
references
References 68 publications
39
300
11
13
Order By: Relevance
“…Our findings that early language skills varied widely but were generally delayed in this ASD sample corroborate results of previous studies, such as Charman et al (2003), Ellis Weismer et al (2010), andLuyster et al (2008). We found a weaker association of vocabulary size with age than found in typically developing children.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings that early language skills varied widely but were generally delayed in this ASD sample corroborate results of previous studies, such as Charman et al (2003), Ellis Weismer et al (2010), andLuyster et al (2008). We found a weaker association of vocabulary size with age than found in typically developing children.…”
Section: Discussionsupporting
confidence: 91%
“…The literature on lexical development in children with ASD raises the same issue. The 'delay' view is supported by the ways lexical development in children with ASD resembles typical lexical development, namely that children with ASD (a) tend to acquire more words in their lexicons as they get older (Charman et al, 2003 ;Smith et al, 2007) ; (b) vary widely in lexicon size (Charman et al, 2003 ;Ellis Weismer et al, 2010 ;Ellis Weismer et al, 2011 ;Luyster et al, 2007 ;Luyster et al, 2008); (c) show a predominance of nouns and roughly the same percentages of nouns, verbs and closed-class terms as typically developing children with similar vocabulary sizes (Charman et al, 2003); (d) exhibit a noun bias in laboratory preferential looking studies (Swenson et al, 2007 ;Tek et al, 2008) ; and (e) manifest high correlations between parent-reported vocabulary scores and directly administered expressive language tests (Ellis Weismer et al, 2010 ;Luyster et al, 2008). On the other hand, the 'deviance ' view is supported by the ways in which lexical development in children with ASD differs from typical development, such as (a) a much higher percentage of severe vocabulary delays (Charman et al, 2003, Ellis Weismer et al, 2011Luyster et al, 2007 ;Luyster et al, 2008) ; (b) much greater variation in rate of vocabulary growth over time (Smith et al, 2007) ; (c) weaker associations between lexicon size and grammatical complexity than late talkers with the same-size lexicons (Ellis Weismer et al, 2011) ; failure to show a shape bias on novel word tasks (Tek et al, 2008).…”
Section: Lexical Development In Typically Developing Childrenmentioning
confidence: 99%
“…Early socialcommunicative abilities such as imitation, joint attention and pretend play are seen as important intervention targets, given the clear deficits observed in young children with ASD and the pivotal role these skills play in development (Lam & Yeung, 2012;Paparella, Goods, Freeman, & Kasari, 2011;Vanvuchelen, Roeyers, & De Weerdt, 2011b). Especially the association of these abilities with language has been studied extensively (e.g., Luyster, Kadlec, Carter, & Tager-Flusberg, 2008;Poon, Watson, Baranek, & Poe, 2012).The present study aims to investigate this association in a large sample of preschoolers with ASD with a more rigorous measurement of the social-communicative abilities than in previous research.Studying language in children with ASD is important, considering it is one of the variables most significantly associated with later outcome (Anderson, Oti, Lord, & Welch, 2009). Moreover a language delay is one of the first symptoms that raises parental concern (Wetherby et al, 2004).…”
mentioning
confidence: 99%
“…En effet, certains enfants TSA arrivent à se baser sur le regard pour coupler des formes phonologiques (la forme sonore du mot) nouvelles avec des objets, mais ils ne parviennent pas toujours à intégrer l'information sémantique (le sens du mot) au sein de leur lexique mental, c'est-à-dire à associer le mot nouvellement acquis à une signification riche et flexible, interconnectée avec celles d'autres mots [16,17]. Cette hypothèse expliquerait pourquoi on observe souvent un vocabulaire en réception anormalement bas par rapport au vocabulaire expressif chez les enfants avec TSA, ainsi que le fait que l'utilisation de mots soit généralement figée et peu productive dans l'autisme [7,18,19].…”
Section: Pragmatique Et Acquisition Lexicale Dans Les Tsaunclassified
“…En fait, ce manque de coordination attentionnelle constitue probablement un facteur prépondérant dans la trajectoire développementale atypique des enfants avec autisme (par exemple, [4]). Or, la capacité à suivre la direction du regard d'autrui, celle de contrôler l'attention conjointe et, plus généralement, de faire preuve de sensibilité aux indices sociaux sont autant de facteurs centraux dans l'acquisition du langage, que ce soit chez les enfants au développement typique ou dans les TSA [5][6][7]. Il se pourrait donc que les problèmes dans l'acquisition du langage dans les TSA soient partiellement causés par cette absence d'attention conjointe ou partagée.…”
Section: Au-delà Du Sens Littéralunclassified